SAT0491 Clinical features and complications in a large international cohort of antimda5 patients: a challenge for the future. (12th June 2018) - Locatelli, F.; Castaneda, S.; Zanframundo, G.; Meyer, A.; Iannone, F.; Giannini, M.; Prieto Gonzalez, S.; Scire, C.; Govoni, M.; Montecucco, C.; Furini, F.; Vega, J.; et al.
Abstract : Background: Anti-MDA5 antibodies are a known set of antibodies observed mainly in dermatomyositis, typically associated with cutaneous involvement, presence and often rapid progression (RP) of interstitial lung disease (ILD) and amyopathic muscle involvement. Despite the increased attention, described cohorts involves only a limited number of cases Objectives: to define clinical characteristics of a large cohort of anti-MDA5 antibodies positive patients Methods: Retrospective assessment of anti-MDA5 positive patients from centres referring to our group Results: 82 anti-MDA5 positive cases (56 females) were collected. In median: onset age was 44 Y (IQR 22.57), diagnostic delay 4 Mo (IQR 1–10), follow-up 13 Mo (IQR 3–43). Fifty-three patients had ILD, that was RP in 24 cases (15 at ILD onset, 9 after ILD onset). Fifthteen ILD patients were admitted in Intensive Care Unit (ICU): 4 were treated with Extracorporeal-Membrane-Oxygenation, 7 with mechanical-invasive and 2 with mechanical-non-invasive ventilation. Forthy-nine patients had muscle involvement (39 symptomatic), 42 arthritis, 54 cutaneous involvement, 9 history of malignancy. Twelve patients died (ILD=7, ILD and sepsis=3, neoplasia=1, not specified=1), 7 of those in ICU Conclusions: In our cohort, ILD was the most frequent finding. A RP of ILD was common, occurring also in ILD with symptomatic/chronic onset. The low rate of survival in ICU raised the problem of follow up and early treatment of ILD. In our cohort arthritis was common and muscle involvement mainly symptomatic. Finally, the high percentage of observed malignancies suggests a careful neoplastic screening and follow up Reference: [1] Labrador-Horrillo M, et al. J Immunol Res2014;2014:290797. Disclosure of Interest: None declared